Effectiveness of short active breaks for reducing sedentary behavior and increasing physical activity among Japanese office workers: one-year quasi-experimental study - Naruki Kitano; Takashi Jindo; Kaori Yoshiba; Daisuke Yamaguchi; Yuya Fujii; Kyohsuke Wakaba; Kazushi Maruo; Yuko Kai; Takashi Arao (Scandinavian Journal of Work, Environment & Health, 2025)

(untitled)
OBJECTIVES: We examined the effects of a one-year multicomponent workplace intervention that introduced short active breaks from prolonged sitting on occupational movement behaviors and health among Japanese office workers. METHODS: This quasi-experimental study was conducted in Tokyo, Japan (2019–2020). In the intervention group (N=172), activity breaks from sitting were introduced to the work schedule (approximately 10 minutes/working hour) together with support strategies to encourage participation (eg, social support, provision of information). Workers in the control group (N=323), who worked at the same company group as those in the intervention group, did not receive any intervention. We evaluated accelerometer-measured sedentary behavior and physical activity during working hours as primary outcomes, and mental health and subjective job performance as secondary outcomes. Propensity score weighting using overlap weights was performed to examine between-group differences in outcomes at one year. RESULTS: At the one-year follow-up assessment, sedentary behaviors during working hours in the intervention group decreased by 24.4 minutes (95% confidence interval 31.6–17.3), with physical activity increasing by a comparable amount (P for group difference <0.05). However, at the one-year follow-up, psychological distress had worsened and work engagement had declined in the intervention group relative to baseline (P for group difference <0.05). CONCLUSIONS: Our findings suggest that this program is a feasible approach to reducing sedentary behavior and promoting physical activity during work hours among office workers. However, methodological limitations prevent the definitive attribution of the effects to the intervention. Further rigorous research is needed to assess its effectiveness and external validity before broad implementation.